Membasmi Koruptor Sejak Usia Dini: Analisis Kurikulum Pendidikan Agama Islam Anti Korupsi di Madrasah - Ahmad Ulul Albab, Hayyan (ACIECE, 2019)
Corruption is rottenness, badness, and depravity. Anti-corruption education is actually veryimportant in preventing corruption and very useful in preventing corruptors. This study aims to find a concrete action or breakthrough in combating corruption from an early age. This study uses a qualitative content analysis method. This research resulted in a concrete action in eradicating corruption with eradicating corruptors in Indonesia can be started by educating the nation's children by instilling anti-corruption morals by referring to the guidelines for organizing Anti-Corruption Education in Madrasah which can be developed by the Kindergarten teachers, the teacher should make serious efforts implanting anti-corruption character through the method of fairy tales